Physicochemical, Microbiological and Organoleptic Characteristics of Rosella Water Kefir with Sucrose Sweetener - Heni Rizqiati; Nurwantoro Nurwantoro; Adelia Maharani Bramadita (Universitas Sebelas Maret (UNS), 2023)
Red rosella is one of the beneficial plants with its flower petals that have a distinctly sour taste. Using rosella in water kefir can enrich its functionality and taste. Rosella water kefir has acidic characteristics derived from rosella and sugar substrates. Sugars such as sucrose in the production of water kefir act as a carbon source for the metabolism of water kefir grains. The higher the added sugar causes the total of good microbes and organic acids in water kefir products to increase, but too high sugar can cause the death of these good microbes so it also affects the nutritional content and taste of the product. Therefore, the best concentration of sugar is needed. This study aims to obtain the best sucrose concentration in producing the best physicochemical, microbiological, and organoleptic characteristics of rosella water kefir. This study used the addition of sucrose at concentrations of 6%, 9%, 12%, and 15% (w/v) with the parameters observed in physicochemical characteristics including total dissolved solids, biomass, CO2 content, and total acid, microbiological characteristics including total lactic acid bacteria and total microbes, and organoleptic characteristics including sweet taste, sour taste, soda sensation, and aroma. The results obtained in this study indicate that increasing the concentration of sucrose in rosella water kefir had a significant effect (p<0.05) on the physicochemical, microbiological, and organoleptic characteristics of sweet and sour tastes. The addition of 12% sucrose was the limit—tolerance for the addition of sugar in rosella water kefir which is also the best treatment.